The Correlation Between Intrinsic Motivation and Students’ Reading Comprehension at Information Systems Study Program of Universitas Muhammadiyah Riau - Khairani Nurjannah; Retno Sutrayani; Silva Iriana Widari; Tia Novani Irawan; Wandi Syahfutra; Novela Nurafrezah (Widya Accarya, 2025)
This research aims to examine the relationship between intrinsic motivation and reading comprehension skills of Information Systems Study Program students at Muhammadiyah Riau University. The research used a quantitative approach with a sample of 62 randomly selected students. The instruments used included an intrinsic motivation questionnaire based on the Motivation Reading Questionnaire (MRQ) and a reading ability test based on TOEFL standards. Data were analyzed using Kolmogorov-Smirnov normality test and Pearson Product Moment correlation. The results showed a weak but statistically significant positive relationship (r = 0.367, p < 0.05) between intrinsic motivation and reading comprehension ability. The findings confirmed the importance of intrinsic motivation in supporting the engagement and development of reading ability, but also showed that other factors such as language skills and reading strategies play a role in comprehending technical texts. The implication of this research is the importance of developing learning strategies that integrate motivation with technical elements to improve students' reading ability holistically.